Bio‐Inspired Non‐Bactericidal Coating Used for Antibiofouling. Issue 2 (23rd November 2018) - Bing, Wei; Tian, Limei; Wang, Yangjun; Jin, Huichao; Ren, Luquan; Dong, Shiyun
Abstract: Inspired by the antifouling properties of soft coral surface, the antifouling film of graphene‐silicone elastomers (GSE) composite materials are prepared and modified with a tentacle structure (TS‐GSE). This antifouling coating has an adjusted elastic modulus, originally low surface energy, and strong electronegativity, and all these physical properties are a benefit to antifouling. The nonbactericidal film of TS‐GSE can expel bacteria through physical interaction, and it is more effective than bactericidal coatings. Moreover, the elasticity deformation of SE is modeled by the standard k‐ε turbulence model. Results indicate this elastic material has a harmonic motion effect through deformation under the fluid flow, and the response frequency is about 10 Hz. The harmonic motion effect makes the elastic surface unstable and provide a foul release basis. Bacteria attachment is tested under both static conditions and dynamic conditions, and results show that the antiadhesion coating of TS‐GSE showed strong antiadhesion activity against both Gram‐negative and Gram‐positive bacteria. This work should not only enhance understanding of elastomers‐based antifouling materials but also facilitate the design and construction of other types of nontoxic foul‐release materials. Abstract : Inspired by the antifouling properties of the soft coral surface, graphene‐SE (GSE) composite materials were prepared with a tentacle structure (TS‐GSE). This material has an adjusted elastic modulus, originally low surface energy and strong electro‐negativity which are a benefit for antifouling. Moreover, this elastic material has a harmonic motion effect under the stimulus of a fluid medium, rendering the elastic surface unstable and foul‐release performances.